PENGETAHUAN REMAJA PUTRI TENTANG PEMERIKSAAN PAYUDARA SENDIRI DI SMA NEGERI 1 BAUMATA KABUPATEN KUPANG TAHUN 2014 - BRINGIWATTY BATBUAL (JURUSAN KEBIDANAN POLTEKKES KUPANG, 2014)
Background, Statistically berast cancer in Indonesia ranks second after cervical cancer. More than 70 percent breast cancer has been found at advanced stage. One of causion this desasew in not early detected is because lack of knowledge about early detection for breast cancer. Aim of thir research ini to knowing and evaluating about prior knowledge and the end knowledge about SADARI with seminar method.Thid research is a descriptive research with pre-post design.Result, Result showing most of respondent (41,2%) has a less prior knowledge about SADARI and 59 % has a good knowledge after seminar.Conclution, tennage knowledge before seminar is still lack and their knowledge after seminar is good enough.